Locus Coeruleus Integrity from 7 T MRI Relates to Apathy and Cognition in Parkinsonian Disorders. Issue 8 (16th May 2022) - Ye, Rong; O'Callaghan, Claire; Rua, Catarina; Hezemans, Frank H.; Holland, Negin; Malpetti, Maura; Jones, P. Simon; Barker, Roger A.; Williams‐Gray, Caroline H.; Robbins, Trevor W.; Passamonti, Luca; Rowe, James
Abstract: Background: Neurodegeneration in the locus coeruleus (LC) contributes to neuropsychiatric symptoms in both Parkinson's disease (PD) and progressive supranuclear palsy (PSP). Spatial precision of LC imaging is improved with ultrahigh field 7 T magnetic resonance imaging. Objectives: This study aimed to characterize the spatial patterns of LC pathological change in PD and PSP and the transdiagnostic relationship between LC signals and neuropsychiatric symptoms. Methods: Twenty‐five people with idiopathic PD, 14 people with probable PSP‐Richardson's syndrome, and 24 age‐matched healthy controls were recruited. Participants underwent clinical assessments and high‐resolution (0.08 mm 3 ) 7 T‐magnetization‐transfer imaging to measure LC integrity in vivo. Spatial patterns of LC change were obtained using subregional mean contrast ratios and significant LC clusters; we further correlated the LC contrast with measures of apathy and cognition, using both mixed‐effect models and voxelwise analyses. Results: PSP and PD groups showed significant LC degeneration in the caudal subregion relative to controls. Mixed‐effect models revealed a significant interaction between disease‐group and apathy‐related correlations with LC degeneration ( β  = 0.46, SE [standard error] = 0.17, F (1, 35) = 7.46, P  = 0.01), driven by a strong correlation in PSP ( β  = −0.58, SE = 0.21, t (35) = −2.76, P  = 0.009). Across both disease groups, voxelwise analyses indicated that lower LC integrity was associated with worse cognition and higher apathy scores. Conclusions: The relationship between LC and nonmotor symptoms highlights a role for noradrenergic dysfunction across both PD and PSP, confirming the potential for noradrenergic therapeutic strategies to address transdiagnostic cognitive and behavioral features in neurodegenerative disease. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society